Kebijakan Bebas Visa Bagi Warga Negara Asing yang Masuk Secara Ilegal dalam Prespektif Hukum Keimigrasian - Elvira Belinda Mantiri; Johanis Steny Franco Peilouw; Lucia Charlota Octovina Tahamata (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2021)
Introductioan: This research discusses the issue of Free Visas made by the government in Presidential Regulation No. 21 of 2016 concerning Visa Free that does have a positive impact such as the increase in the number of tourists that is felt in economic growth, as well as foreign exchange countries. But it also has a negative impact, namely free visas, visas made by citizens such as an overstay visit visa, or workers who enter to work in Indonesia illegally.Purposes of the Research:  Analyze and review visa-free policies for the entry and exit of foreign national)Methods of the Research: This study uses a normative juridical method with the legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literatureResults / Findings / Novelty of the Research: The Visa Free Policy made by the government does have a positive impact such as the increase in the number of tourists is very much felt in economic growth, as well as the country's foreign exchange. But it also has a negative impact, namely the abuse of visa-free committed by foreign nationals, such as the abuse of an overstay visit visa, or foreign workers who enter to work in Indonesia illegally, this can also affect the country's sovereignty, especially in the social and social fields. economy therefore the abuse of visa-free must be a major concern for the government to be able to solve the problem.